The relationship between accessibility of retail seeds and diet diversity: a multi-level structural equation model applied to ethnic minority farmers in northern Vietnam - Nguyen, Lan Thuy T.; van den Berg, Marrit; Douma, Jacob Bob; Stomph, Tjeerd Jan (Springer Science+Business Media, 2025)
Undernutrition remains a critical issue among ethnic minorities in northern Vietnam, likely due to limited diet diversity. Our study examined the accessibility of retail seeds, its link to diet diversity, and the relative contribution of food and seed market access and income on diet diversity, specifically targeting diversity in vegetables and legumes. We utilized a comprehensive dataset, comprising a household survey conducted with nearly 500 respondents, a community survey in 38 villages, and a market survey of 14 marketplaces. Using the multi-level structural equation modelling (MSEM) method, we empirically validated a conceptual model linking diet diversity with food and seed market access and satisfaction with off-farm seed sources, where the latter two are aspects of accessibility of retail seeds. The linkages are mediated by crop diversity at both village and household levels, and household wealth. Results showed that retail seeds played a key role in enhancing crop diversity, while self-saved seeds remained the dominant seed source. Crop diversity influenced diets directly through the subsistence pathway and indirectly through the income pathway, though the latter effect was smaller. Household wealth also improved diet diversity directly and indirectly by promoting crop diversity, suggesting that income sources outside of vegetable and legume production are crucial for supporting diverse diets. Market access enhances diet diversity through food purchases and indirectly through crop diversity, yet this indirect effect is much smaller. Its overall impact on crop diversity was more nuanced due to multiple influences. Furthermore, farmers’ satisfaction with off-farm seed sources indirectly improved diet diversity by increasing crop diversity. Our findings suggest that promoting crop diversity and supporting food purchases are both essential for improving diets. Encouraging integrated seed systems that recognize the role of both farmer and formal seed systems could further enhance crop diversity and diet diversity.